Implementasi Sistem Barcode pada Perusahaan Perkebunan Kelapa Sawit untuk Meningkatkan Efisiensi Serta hubungannya dengan Smart People : Implementasi Sistem Barcode pada Perusahaan Perkebunan Kelapa Sawit untuk Meningkatkan Efisiensi Serta hubungannya dengan Smart People - NASUTION, ANISAH (Indonesian Journal of Electrical Engineering and Renewable Energy (IJEERE), 2023)
The use of innovative technology such as the barcode system has the potential to increase the efficiency of palm oil companies and support the realization of smart people. To better understand the impact of barcode system implementation, a qualitative study was conducted. In this study, a qualitative research method was used with a case study approach to explore the implementation of a barcode system in oil palm plantation companies. The qualitative research method was chosen because it can produce more in-depth data and prioritize face-to-face interviews with several informants to get a true and in-depth picture of various perspectives and situations. This study aims to determine the impact of implementing a barcode system on efficiency and smart people. This study used a sample of 4 companies. Based on validity, reliability, relevance of findings, contribution to knowledge and quality of writing, the success percentage of qualitative research is 83%. The results of the study show that the implementation of the barcode system has an impact on efficiency and improvement of human resources through the development of smart people. These findings can be useful for further development of the barcode system, and it is recommended that other palm oil companies adopt this technology.